2011
DOI: 10.1002/per.811
|View full text |Cite
|
Sign up to set email alerts
|

PERSOC: A Unified Framework for Understanding the Dynamic Interplay of Personality and Social Relationships

Abstract: The interplay of personality and social relationships is as fascinating as it is complex and it pertains to a wide array of largely separate research domains. Here, we present an integrative and unified framework for analysing the complex dynamics of personality and social relationships (PERSOC). Basic principles and general processes on the individual and dyadic level are outlined to show how personality and social relationships influence each other and develop over time. PERSOC stresses the importance of soc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
311
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 254 publications
(323 citation statements)
references
References 131 publications
(226 reference statements)
12
311
0
Order By: Relevance
“…Finally, the TESSERA framework leads to novel insights into existing developmental phenomena, which were not addressed in previous theories (e.g., Back, Baumert, et al, 2011;Hennecke et al, 2014;Mischel & Shoda, 1995;, such as why correlated change among Big Five traits and motivational orientations differ and why different patterns of personality continuity and change are observed across the adult life span. In addition to normative patterns of personality development due to normative life transitions with similar situations and expectancies Neyer et al, 2014), individual differences in the strength and direction of development can be explained through differences in personal or environmental factors that affect the TESSERA components.…”
Section: Contribution Of the Tessera Framework And Unique Predictionsmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, the TESSERA framework leads to novel insights into existing developmental phenomena, which were not addressed in previous theories (e.g., Back, Baumert, et al, 2011;Hennecke et al, 2014;Mischel & Shoda, 1995;, such as why correlated change among Big Five traits and motivational orientations differ and why different patterns of personality continuity and change are observed across the adult life span. In addition to normative patterns of personality development due to normative life transitions with similar situations and expectancies Neyer et al, 2014), individual differences in the strength and direction of development can be explained through differences in personal or environmental factors that affect the TESSERA components.…”
Section: Contribution Of the Tessera Framework And Unique Predictionsmentioning
confidence: 98%
“…In contrast, associative processes (i.e., the number of state repetitions together with reactions) should predict changes in implicit representations and these changes should be stronger when compared with explicit representations. Previous theories predicted that repeated states predict personality trait development (Back, Baumert, et al, 2011;Mischel & Shoda, 1995;Roberts, 2006Roberts, , 2009, hence did not specify associative and reflective processes and did not distinguish development of implicit, behavioral, and explicit trait manifestations. • • Substantial personality change can occur in middle and late adulthood, if (a) enough "opportunities" to experience new situations exist (e.g., life experiences typically experienced during young adulthood, entering the work force), (b) more repetitions occur to elicit changes in implicit associations compared with young adulthood, and (c) novel states are reflected as novel instead of personality-congruent like during identity confirmation.…”
Section: Contribution Of the Tessera Framework And Unique Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, similar to Study 1, participants who exhibited a stronger hindsight bias also showed a stronger increase in their usage of more valid cues. used approach for gathering zero-acquaintance judgments, it is limited because it does not represent the natural stream of behaviors (Back, Baumert, et al, 2011;Baumeister, Vohs, & Funder, 2007) that one typically observes. Thus, other situational contexts (e.g., videos of targets, actual interactions), will have to be examined in future studies.…”
Section: Limitationsmentioning
confidence: 99%